The intermediate situation. On affection and time in Michel Henry - Barrientos, John David (Investigaciones Fenomenológicas, 2014)
When we go back-by means of the epoché of the world, following Michel Henry-towards the originary “how” of all manifestation (videor), we stumble once and again upon the phenomenological situation of the body. The body is, then that originary hinge by means of which I manifest world in a continuous resistance. It will be, as well, within my own body where I am always aware of oneself, according to my own affection (self-affection, not previously constituted). Thus, the material condition of the body will be that of my internal body, or subjective body-as Henry initially read in Maine de Biran-or that of my flesh, as Henry himself would later say. Bearing all this in mind, the intermediate situation of one’s own affection, of this body of mine, with regard to the world and the videor, turns out to be an appropriate medium to attempt a preliminary study of the problematic situation of the internal time of affection. For this purpose, we shall revise the analysis offered by Michel Henry in Material Phenomenology and in Incarnation, indicating possible aporias, as well as alternatives to these last ones. Cuando, siguiendo a Michel Henry, retrocedemos en una epoché hacia el “cómo” originario de toda manifestación (videor), tropezamos una y otra vez con la situación fenomenológica del cuerpo. El cuerpo es, pues, esta bisagra originaria a través de la cual yo manifiesto el mundo en continua resistencia. También será dentro del propio cuerpo donde uno será siempre autoconsciente, de acuerdo con la propia afección (autoafección, no constituida previamente). Por eso, la condición material del cuerpo será la de mi cuerpo interior o cuerpo subjetivo, de acuerdo con la lectura inicial que Henry hace de Maine de Biran; o de mi carne, como dirá el mismo Henry más tarde. Teniendo en cuenta todo ello, la situación intermedia, situación de la afección propia y la de mi cuerpo en relación con el mundo y el videor, resulta ser un medio apropiado para emprender un estudio preliminar de la problemática situación del tiempo interno de la afección. Para ello, revisaremos el análisis que Michel Henry ofrece en Material Phenomenology y en Incarnation, indicando las posibles aporías, así como posibles alternativas.